Remote Sensing the Forest - Singh, R. S. (Indian Forester, 1970)
Remote sensing by a media other than ordinary black and white photography is comparatively new science and it has wide applications in different fields. Its usefulness in forestry has been brought about in this paper. Different kinds of remote sensore are briefly sated. Ways and means of species identification and disease detection, time and season of photography, methods of finding tree count, crOwn diameter, tree heights and timber volume, film types and spectral ranges most suitable for forestry are discussed.